On the Darboux-Nijenhuis variables for the open Toda lattice - Grigoryev, Y.A.; Tsiganov, A.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
We discuss two known constructions proposed by Moser and by Sklyanin of the Darboux-Nijenhuis coordinates for the open Toda lattice.